The curious non-advent of codetermination in Belgium: A focus on the Christian trade union - Stan de Spiegelaere (European Trade Union Institute (ETUI), 2023)
Belgium is one of the few EU-15 countries with no system of involving employee representatives in the strategic management of a company. The post-second World War social pact created extensive institutions for information, consultation and collective bargaining at the company, sector and country level but did not envisage, for example, employees on company boards. At the same time, one of the two large trade union confederations (the ACV-CSC) with its historical links to the long-time dominant Christian democratic party, has been in favour of such a system for a long time. In this working paper, the post-war views of the ACV-CSC on workers on the board and economic democracy are presented and discussed. When considering the different periods of debate and activism, clear evolutions in thinking are evident. Ethical arguments in general and arguments drawn from Christian teaching decrease markedly in importance, while economic and pragmatic argumentation becomes more prominent. Further, the Belgian Christian trade union's recent rejection of the idea of codetermination is a rupture with its previous positions, but it seems that these positions never really enjoyed the support of most of their members anyway.
Keywords: 330; Gewerkschaft; Christliche Sozialethik; Mitbestimmung; Ideengeschichte; Belgien